Magical urbanism Latinos reinvent the US city - Davis, Mike 1946-2022 (Verso, 2001)
A fascinating account of the Latinization of the US urban landscape, Magical Urbanism forcefully shows that this is a demographic and cultural revolution with extraordinary implications. Davis focuses on the great drama of how Latinos are attempting to translate their urban demographic ascendancy into effective social power. Pundits are now unanimous that Spanish-surname voters are the sleeping giant of US politics, yet electoral mobilization alone is unlikely to redress the increasing income and opportunity gaps between urban Latinos and suburban non-Hispanic whites. Therefore, in Los Angeles and elsewhere, the militant struggles of Latino workers and students are reinventing the American left. Fully updated throughout, and with new chapters on the anti-immigrant backlash, the impact of climate change on the urban Southwest, and the exploding counter-migration of Anglos to Mexico, Magical Urbanism is essential reading for anyone who wants to grasp the future of urban America.
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Alltag, Brauchtum; City and town life -- United States; Hispanic Americans -- Attitudes; Hispanic Americans -- Social conditions; Hispanic Americans -- Social life and customs; Innenstadt; Ethnische Identität; Stadt; Soziologie; Hispanos; Chicanos; Ethnische Beziehungen; USA; United States -- Civilization -- Hispanic influences